Evaluation of Hemostatic Parameters in Tumor-Bearing Dogs - Anjos, Denner Santos dos [UNESP]; Santilli, Juliana; Vital, Aline Fernandes; Oliveira, Jessica Rodrigues de [UNESP]; Rosa Sobreira, Marcia Ferreira da [UNESP]; Magalhae, Georgia Mode; Calazans, Sabryna Gouveia [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (Univ Fed Rio Grande Do Sul, 2018)
Background: Hemostatic alterations are commonly detected in canine cancer patients. However, few studies have described hemostatic dysfunction in dogs with different tumor subtypes. In Veterinary Medicine, the state of hypercoagulability is hardly diagnosed alive, since laboratory exams for evaluate hemostatic function are not always requested. Due to importance of homeostatic disorders in cancer patients, this study aimed to evaluate hemostatic alterations such as platelet count, activated partial thromboplastin time (aPTT), prothrombin time (PT) and fibrinogen in tumor-bearing dogs. Materials, Methods & Results: From the 55 dogs evaluated, 30 had mammary carcinoma, 6 visceral hemangiosarcoma 9 high-grade cutaneous mast cell tumor and 10 multicentric lymphoma. The results were compared to a control group composed by 10 Beagle dogs. Thrombocytosis was observed in 26.6% (8/30) of mammary carcinoma group and thrombocytopenia in 10% (3/30). The patients with hemangiosarcoma and mast cell tumor did not reveal thrombocytosis, however, thrombocytopenia was present in 16.6% (1/6) and 33% (3/9), respectively. Three dogs with multicentric lymphoma showed thrombocytopenia and other three showed thrombocytosis. From patients with thrombocytosis, one was classified as severe thrombocytosis (1077 x 10(3)/mu L). Therefore, there were no statistically significant associations between neoplasia group with control group (P > 0.05). Regarding the aPTT and PT evaluation, mammary carcinoma (P = 0.0005), hemangiosarcoma (P = 0.033) and mast cell tumor (P = 0.012) patients showed statistical difference for aPTT, while the evaluation for PT was not significant (P > 0.05). We grouped all patients as a twnor group and compared to the control group. It was possible to observe increased aPTT and PT in 89% (49/55) and 50.90% (28/55) respectively, in tumor group compared to normal. A total of 47.27% (n = 26) of the patients with tumors presented increased aPTT and PT concomitantly. In the present study, 14.54% of the patients presented elevated levels of fibrinogen associated with increased aPTT. However, only the mast cell tumor group was statistically significant (P = 0.043). Discussion: Hemostatic alterations can be found in dogs with cancer and when these alterations occurs, can be directly associated with tumoral non-invasive actions called as paraneoplastic syndrome. However, the hemostatic paraneoplastic syndrome is poorly reported in veterinary medicine, with limited number of papers describing this condition. Our results indicated that the presence of thrombocytosis in patients with tumors could be related with the production of granulocytemacrophage colony stimulating factors (GM-CSF) and IL-6 by tumor cells. A total of 26 patients with tumors presented increased aPTT and PT concomitantly, confirming that hemostatic dysfunction is a common alteration in dogs with neoplasia. However, despite alterations in coagulation parameters, there were no clinical manifestations of bleeding such as petechial or bruising in these patients. The increased fibrinogen and aPTT can be caused by a systemic inflammatory reaction mediated by pro-inflammatory cytokines produced by tumors cells. Based on that, 14.54% of the animals presented elevated levels of fibrinogen associated with elevated aPTT suggesting that these patients are associated with systemic inflammation and tumor progression. This study suggested that bearing-tumors patients shows important hemostatic dysfunctions, elucidating the clinical importance of these results in veterinary medicine.
Keywords: aPPT; dogs; fibrinogen; hemostatic dysfunction; platelets; PT